2017
DOI: 10.1038/s41598-017-07479-z
|View full text |Cite
|
Sign up to set email alerts
|

Antibody-induced dimerization of FGFR1 promotes receptor endocytosis independently of its kinase activity

Abstract: Fibroblast growth factors (FGFs) and their plasma membrane-localized receptors (FGFRs) play a key role in the regulation of developmental processes and metabolism. Aberrant FGFR signaling is associated with the progression of serious metabolic diseases and human cancer. Binding of FGFs to FGFRs induces receptor dimerization and transphosphorylation of FGFR kinase domains that triggers activation of intracellular signaling pathways. Following activation, FGFRs undergo internalization and subsequent lysosomal de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 48 publications
3
37
0
Order By: Relevance
“…Fully glycosylated extracellular domains of FGFRs fused to the Fc fragment of human IgG1: FGFR1 IIIc (FGFR1‐Fc), FGFR2 IIIc (FGFR2‐Fc), FGFR3 IIIc (FGFR3‐Fc), and FGFR4 (FGFR4‐Fc), and the extracellular part of FGFR1 lacking the N‐terminal D1 domain (FGFR1 D2‐D3) were produced as described previously by our group [48]. FGFR1 GST‐D1 was expressed in E. coli BL21 CodonPlus (DE3)‐RIL (Agilent Technologies, Santa Clara, CA, USA) and purified with use of Glutathione Sepharose column as described previously [5,6,49].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fully glycosylated extracellular domains of FGFRs fused to the Fc fragment of human IgG1: FGFR1 IIIc (FGFR1‐Fc), FGFR2 IIIc (FGFR2‐Fc), FGFR3 IIIc (FGFR3‐Fc), and FGFR4 (FGFR4‐Fc), and the extracellular part of FGFR1 lacking the N‐terminal D1 domain (FGFR1 D2‐D3) were produced as described previously by our group [48]. FGFR1 GST‐D1 was expressed in E. coli BL21 CodonPlus (DE3)‐RIL (Agilent Technologies, Santa Clara, CA, USA) and purified with use of Glutathione Sepharose column as described previously [5,6,49].…”
Section: Methodsmentioning
confidence: 99%
“…The extracellular domain of FGFR1 contains three immunoglobulin‐like domains D1, D2, and D3. The D1 domain fulfills a regulatory function preventing FGFR1 from autoactivation in the absence of FGFs [3–6]. The D2 and D3 domains form FGF binding sites [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1a). Growth factor binding leads to FGFR1 trans-activation and effectively stimulates internalization of FGF-FGFR1 complexes [17,46,47]. To study whether FGF1 binding to SBP-FGFR1 accelerates uptake of the receptor, U2OS-SBP-R1 cells were pre-labeled with streptavidin-AF555 and then incubated in the presence or absence of FGF1.…”
Section: Fgfr1 Interactome Reveals Galectin Family Members As Novel Fmentioning
confidence: 99%
“…1d, lanes 5 and 6). We and others have recently demonstrated that in the absence of FGF1 FGFR1 is present in high molecular weight complexes that likely represent unliganded receptor dimers [47][48][49][50][51]. To study whether isolated SBP-FGFR1 retained its ability to form high molecular weight complexes we have performed streptavidin-agarose pull down and eluted bound proteins with biotin.…”
Section: Fgfr1 Interactome Reveals Galectin Family Members As Novel Fmentioning
confidence: 99%